Biopolitics of COVID-19: capitalist continuities and democratic openings - Schubert, Karsten (2022)
Abstract: "Biopolitics" has become a popular concept for interpreting the COVID-19 pandemic, yet the term is often used vaguely, as a buzzword, and therefore loses its specificity and relevance. This article systematically explains what the biopolitical lens offers for analyzing and normatively criticizing the politics of the coronavirus. I argue that biopolitics are politics of differentiated vulnerability that are intrinsic to capitalist modernity. The situation resulting from the COVID-19 pandemic is, therefore, less of a state of exception than it might appear; COVID-19 is a continuation and intensification of the capitalist biopolitics of differentiated vulnerability. In order to critically evaluate this situation, the article proposes the concept of "democratic biopolitics" and shows how it can be used, among others, for a queer critique of the differentiated vulnerabilities that are produced by the coronavirus and its capitalist governance. In contrast to widespread interpretations of democratic biopolitics that focus on collective care in communities, this article highlights the role of the state and of the redistribution of political power and economic resources as key for biopolitical democratization